Growth in East Asia : What We Can and What We Cannot Infer From it - Sarel, Michael (IMF Working Papers; Working Paper, 1995)
This paper examines the different arguments raised by the studies that addressed the East Asian growth experience. The original arguments presented in this paper are all on the negative side, highlighting problems associated with some of the possible explanations for the East Asian miracle. The paper concentrates mainly on four dimensions of the debate about the East Asian growth experience: (i) The nature of economic growth intensive or extensive?; (ii) The role of public policy and of selective interventions; (iii) The role of high investment rates and a strong export orientation as possible engines of growth; and (iv) The importance of the initial conditions and their relevance for policy.